ANALISIS DISTRIBUSI DANA DESA TERHADAP PEMERATAAN PEMBANGUNAN INFRASTRUKTUR ANTAR DUSUN DI DESA SUWATU KECAMATAN TANON KABUPATEN SRAGEN - Nazifa Qurratu Aini; Rina Martini (Journal of Politic and Government Studies, 2026)
This study examines the distribution of Village Funds toward equitable infrastructure development among hamlets in Suwatu Village, Tanon District, Sragen Regency. The Village Fund policy, sourced from the State Budget and implemented since 2015 under Law Number 6 of 2014 concerning Villages, aims to promote welfare improvement and accelerate development at the village level. However, equitable distribution of development benefits among hamlets within a single village remains an unresolved issue, as evidenced by the 2024 Village Development Index (IPD) gap among Hamlet Ngijo (73.5/Advanced), Hamlet Banaran (60.5/Developing), and Hamlet Mlangse (55.5/Underdeveloped). The purpose of this study is to analyze the management of Village Funds in infrastructure development in Suwatu Village. Furthermore, this study aims to identify the factors considered in Village Fund utilization and to analyze the equity of infrastructure development among hamlets. This study uses Rubin's (2019) Budget Politics theory as an analytical framework, which is operationalized through budget governance indicators adapted from Mardiasmo (2021) using a descriptive qualitative approach. Data collection was conducted through in-depth interviews, field observations, and documentation involving village officials, members of the Village Consultative Body (BPD), and community representatives from all three hamlets. The findings indicate that Village Fund management in Suwatu Village has not fully achieved equitable and just development. Several fundamental problems were identified, namely the fund allocation formula was not transparently communicated to the community, Village Deliberation forums were still dominated by certain groups causing the aspirations of underdeveloped hamlets to go unheard, and technical feasibility along with proximity to the village center were more influential in shaping budget distribution than the officially established criteria. These conditions created inequality across three dimensions: inter-area equity, inter-sector equity, and inter-social group equity.Based on these findings, this study recommends that the Suwatu Village government improve the Village Deliberation mechanism to be more inclusive and not dominated by certain groups, prioritize budget allocation to underdeveloped hamlets proportionally based on IPD data, and increase budget information transparency to all layers of society, especially in hard to-reach hamlets. Strengthening oversight based on actual results, not just the completeness of administrative documents, is also key to promoting equitable development.